: Bahasa Inggris - Muchamad Bima Akbar Fauzan; Esti Yuli Widayanti; Rihab Wit Daryono (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Problem-Based Learning (PBL) and Cooperative Learning (CL) methods have an important role in improving problem-solving abilities. In the PBL method, students are invited to face real problems with problem-solving skills in finding solutions. Meanwhile, in CL, students work in small groups and share knowledge to achieve deeper understanding. The aim of this research is for students to improve their problem-solving abilities through PBL and CL learning methods. This research is an experimental type with data collection techniques in the form of pretest and posttest in experimental classes 8A and 8B. Normality test data analysis uses Shapiro Wilk, while hypothesis testing uses independent and paired sample t-tests and N-gain tests. The results of this study show that the PBL and CL methods can improve students' problem-solving abilities with experimental class 8A (PBL) learning outcomes of 77.125%; while for experimental class 8B (CL) 71.490%. Meanwhile, the independent sample t-test showed that there were no significant differences in the pre-test and post-test learning results with ρ-value = 0.758 and 0.347 (>0.05). The conclusion in this research is that there is no significant difference in problem-solving abilities in the concept of tolerance through PBL and CL. Furthermore, the implications of this research emphasize real problems that require a tolerant approach. This research recommends teachers in implementing an important learning model by using case studies about interreligious conflicts in society and how to apply the principles of tolerance in resolving these conflicts.